Esketamine Nasal Spray: new hope for the rapid reduction of depressive symptoms? Review article - Ana Cristina Leite Campos (2022)
Major depressive disorder (MDD) is a common psychiatric illness with a devastating impact on all aspects of life. Approximately, 30% of MDD patients fail to achieve remission despite treatment with at least two oral antidepressants and hence are considered to have treatment-resistant depression (TRD). MDD is commonly associated with suicide. Up to 60% of patients experience suicidal ideation and 10% to 20% attempt suicide over their lifetime. There was no approved medication for the rapid reduction of depressive symptoms in patients at imminent risk of suicide. Current optimal care for these patients in crisis includes oral antidepressants, which require 4-6 weeks for optimal effect, along with hospitalization, although its benefits are short-lived. Esketamine nasal spray, an N-methyl-D-aspartate (NMDA) receptor antagonist, was recently approved in the United States of America and European Union for TRD in adults and as an acute short-term treatment for the rapid reduction of symptoms of MDD, including suicidal ideation, in patients at imminent risk for suicide. Safety and tolerability of intranasal esketamine was acceptable, with generally mild and transient adverse effects, the most reported being dizziness, nausea, dissociation, and increased blood pressure. Given the potential for misuse and abuse, esketamine should be closely monitored. Nonetheless, esketamine nasal spray emerged as a new hope for bridging the efficacy gap created by the delayed onset of action of standard antidepressants in this vulnerable population.